Building Renovation: Which Kind of Guidelines could be Proposed for Policy Makers and Professional Owners?. (November 2015) - Cappelletti, Francesca; Mora, Tiziano Dalla; Peron, Fabio; Romagnoni, Piercarlo; Ruggeri, Paolo
Abstract: IEA IBC Annex 56 methodology provides the basis for the assessment and evaluation of energy related renovation options of residential building stock, first and foremost with respect to cost, energy use and carbon emissions. Furthermore, it allows also for a broader approach going beyond cost effective reduction of carbon emissions and energy use by taking into account co-benefits achieved in a renovation process. Besides impact indicators for primary energy use, carbon emissions and costs it also provides a methodological framework for integrating at least embodied energy use for renovation measures as part of a lifecycle impact assessment. The methodology and resulting fundamentals for renovation standards have to be applicable to different climatic and country specific situations. The Guideline for policy makers proposed by the Annex 56 gives useful information and suggestions to the drafting of legislative and administrative measures, at the national or local level, for reducing the amount of energy consumption and greenhouse gas emissions in renovation of residential buildings. The reachable saving targets must be defined in agreement with the actors in the energy market, as the owners and / or the managers of buildings, but policy makers must be aware of their responsibility in defining cost effective levels for nearly zero energy or emissions building renovation, using a life cycle perspective, and the relevance of preparing adequate financial packages to support ambitious levels for building renovation. Furthermore, the Guideline for professional owners shall report outlines key drivers for building retrofit and use and the resulting impacts on energy consumption. This Guideline shall describe building and energy efficiency trends specific to the residential building sectors.